Service quality and global competitiveness: evidence from global service firms. Issue 6 (4th October 2017) - Sun, Wenbin; Pang, Jing
Abstract : Purpose: The purpose of this paper is to explore the relationship between service quality and firms' global competitiveness in the service industry. A set of moderating effects is formulated to further reveal how the relationship varies under different situations. Design/methodology/approach: This paper tests the model with data collected from multiple sources such as World's Most Admired Companies and COMPUSTAT. Two types of robust regressions for panel data are employed in the empirical model estimation. Findings: Service quality is found to significantly drive global competitiveness. Specifically, its impact is stronger for large service firms and when the global environment is characterized as low munificence, high dynamism, or high complexity. Practical implications: The paper provides a set of implications for managers of service firms regarding global expansion and quality management. It generates useful guidelines of maximizing the power of service quality when a firm's global competitive advantage is considered. Originality/value: This paper takes the first attempt to formulate service quality's influence on firm's global competitiveness with a consideration of specific situational factors.